Discomfort relief after paracetamol administration in febrile children admitted to a third level paediatric emergency department - Chiappini, Elena; Bestetti, Matilde; Masi, Stefano; Paba, Teresa; Venturini, Elisabetta; Galli, Luisa (Frontiers in Pediatrics, 2023)
Background: international guidelines recommend treating fever in children not at a predefined body temperature limit but based on the presence of discomfort. However few studies evaluated discomfort relief after administration of antipyretics in children. Methods: Between 1st January and 30th September 2021 a single-center prospective observational study was performed in febrile children consecutively admitted to a pediatric emergency department and treated with paracetamol orally. For each child, body temperature, presence and severity of discomfort, defined using a previously published semiquantitative likert scale, were evaluated at baseline and 60 minutes after administration of paracetamol, and differences were analyzed. Results: 172 children (males: 91/172; 52.9%; median age: 41.7 months) were included. Significant reductions in body temperature (median body temperature at T0: 38.9°C; IQR: 38.3-39.4, median body temperature at T60: 36.9°C; IQR: 36.4-37.5; P<0,0001), and in the level of discomfort (proportion of children with severe discomfort at T0: 85% and at T60:14%; P<0,0001) were observed. Severe discomfort at T60 persisted in a minority of children (24/172; 14%) and it was not related to body temperature values. Conclusions: paracetamol in febrile children is associated not only with significantly reduction in body temperature but also with discomfort relief.